A history of language philosophies - Formigari, Lia, 1931- (Amsterdam studies in the theory and history of linguistic science. Studies in the history of the language sciences, 2004)
Theory and history combine in this book to form a coherent narrative of the debates on language and languages in the Western world, from ancient classic philosophy to the present, with a final glance at on-going discussions on language as a cognitive tool, on its bodily roots and philogenetic role. An introductory chapter reviews the epistemological areas that converge into, or contribute to, language philosophy, and discusses their methods, relations, and goals. In this context, the status of language philosophy is discussed in its relation to the sciences and the arts of language. Each chapte.